PENYULUHAN DAN PENDAMPINGAN PENANGANAN KOMPLAIN PADA PT CIPTA DAYA GEMILANG SURABAYA - Nugroho, Novianto Eko; Yulianto, Anton Eko (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2023)
The purpose of community service carried out through counseling and assistance in handling complaints at PT Cipta Daya Gemilang Surabaya is to further improve the quality of marketing personnel in handling complaints at the company. The company here will be introduced to how to take steps in dealing with complaints that occur against the company. The method of implementing activities through four stages, namely preparation, counseling on complaint handling materials, monitoring and evaluation. The results of this activity show that there are still many step-by-step observations that must be addressed by this company to further improve the quality of salespeople in finding and maintaining existing customers.